Evaluation of non-formal education management in Maluku Province, Indonesia - Patrisius Rahabav; Threesje Roza Souisa (Institute of Advanced Engineering and Science, 2021)
The study was aimed at evaluating the management of non-formal education institution in Maluku Province. Mixed methods were applied to conduct the study with the population included all 24 accredited non-formal education institutions in Maluku Province in 2017-2018. The non-formal institutions namely Central Maluku Regency 2 Learning Centre Community Activities (PKBM), Southeast Maluku Regency 2 Course and Training Institute (LKP), and 1 PKBM, Buru Regency 2 LKP, and 1 PKBM, Tanimbar Islands Regency 6 PKBM and Ambon City 3 LKP, 6 PKBM and 1 Learning Activity Center. The sample of this study was 24 non-formal education institutions (population sample) with census techniques, and two educators and two learning residents were also involved be interviewed. In collecting the data, several instruments were implemented such as non-test techniques in the form of assessment rubrics, observation, interviews, and documentation studies. In analyzing the data, the context, input, process and product (CIPP) was used as the bases theory and it was analyzed through quantitative and qualitative descriptive analysis ways. The results of this study reported that non-formal education institutions in Maluku Province did not optimally in applying the principles of good governance in the institution management and it was categorized in low level based on the CIPP model of evaluation.